Problematika Kajian Alquran di Era Modern: Studi Pemikiran ‘Abīd al-Jābirī - Miftah Khilmi (JOURNAL OF QUR'AN AND HADITH STUDIES, 2018)
This paper examines a number of problems in Qur’anic studies in the perspective of ‘Abīd al-Jābirī. By using descriptive analytic method, the writer discusses issues about the Qur'an, takwil, interpretation, and the role of reason towards revelation. This study finds that al-Jābirī in discussing these issues combines normative Qur'anic considerations with empirical and rational considerations, to provide answers to religious perspectives whiches relevant to the demands of the times.